Effect of Betaine Supplementation on Growth Performance and Liver Function Test of Growing Murrah Buffalo Calves - Kumar, Sudhir; Yadav, Satya Prakash; Chandra, Gulab; Sahu, Dev Saran; Kumar, Raj; Maurya, Prem Sagar (Indian Journal of Animal Nutrition, 2022)
This study aimed to observe the effect of betaine (BET) supplementation on the growth, immunity, and blood metabolites of Murrah buffalo calves. Twenty-one Murrah buffalo calves with body weight (BW) (98.70 Â± 1.31 kg) and age (8.12 Â± 0.55 months) were selected and randomly distributed into three groups, 7 calves in each group. The diet of all three groups was the same except that the respective group additionally supplemented with 0, 7, and 14 g/d BET during 90 d of the experiment period. The BW and DMI were recorded on fortnightly intervals. Blood samples were taken on fortnightly intervals for the estimation of liver enzymes. There was an improvement (P<0.05) in the BW and average daily gain (ADG) observed in calves receiving 7 or 14 g/d BET. However, dry matter intake (DMI) was unaffected with the supplementation BET. Feed conversion ratio (FCR) was significantly (P<0.05) lower in group supplemented with betaine either dose 7 or 14 g/d than in the control group. No effect of dietary BET addition in the diets of calves was observed on the alkaline phosphatase (ALP), alanine aminotransferase (ALT), and aspartate aminotransferase (AST). The results of our study indicate that supplemental BET may play a role in regulating the growth of growing Murrah buffalo calves.Â